2009
DOI: 10.1111/j.1600-051x.2009.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis and nosocomial lower respiratory tract infection: preliminary findings

Abstract: A marginal association between periodontitis and LRTI was found when smoking, age and length of hospitalization were included as covariates. Patients with LRTI had a high frequency of suspected bronchoaspiration and this could explain the possible association of periodontal disease and LRTI found in this and other studies. Additional studies are needed to further clarify the possible relationship between periodontal disease and LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
1
16
0
1
Order By: Relevance
“…This topic is still controversial in the literature. Some studies corroborate these positive findings, 15,20‐22,26,28 while others do not support the hypothesis that the presence of periodontitis is positively associated with NP 23‐25 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This topic is still controversial in the literature. Some studies corroborate these positive findings, 15,20‐22,26,28 while others do not support the hypothesis that the presence of periodontitis is positively associated with NP 23‐25 …”
Section: Discussionmentioning
confidence: 95%
“…To estimate the sample size calculation, for a study power of 90%, 95% confidence interval (95% CI), ratio of 1:3 between cases and controls was used with a variation range from 1.7 to 3.4 times the odds of an individual with periodontal disease developing NP 26 . The estimated minimum sample size was 298 individuals, 75 cases of NP and 223 controls.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, other features strengthen the method, lending more quality to the study and granting it internal validity. The cutoff point established by the World Health Organization classification was used to define LBW, 20 and the criteria used for the classification of periodontal disease has good specificity and has been used in many other studies linking periodontitis to systemic conditions 23,28,34‐39 . In this context, given the current evidence on reference values ​​for gestational glycemic levels and the findings of this study that showed the overshadowing influence of maternal glycemic level in the relationship between periodontitis and LBW, mainly in mothers with an HbA1c <5.6 but also in those with an HbA1c ≥5.6 and <6.5%, it is important to highlight the need for accurate glycemic levels when studying the oral health status of females during pregnancy.…”
Section: Discussionmentioning
confidence: 85%
“…123 Patients with periodontitis have more than a 3-fold higher risk of having lower respiratory tract infection than those without periodontitis among hospital patients. 124 Among nursing home residents, those without oral health care have 3.6 times higher mortality from pneumonia than those who were assigned oral hygiene care by nursing assistants. 125 Systematic reviews published in 2003, 126 2006, 127 2008, 128 and 2013 129 explored whether oral health care interventions in frail older persons in nursing homes or at hospitals could prevent aspiration pneumonia, and concluded that Mechanical oral hygiene and local chemical disinfection with antiseptics or antibiotics prevent aspiration pneumonia.…”
Section: Aspiration Pneumoniamentioning
confidence: 99%